Live Attenuated Streptococcus pneumoniae Strains Induce Serotype-Independent Mucosal and Systemic Protection in Mice - Roche, Aoife M. (American Society for Microbiology, 2007)
Streptococcus pneumoniae is an important human pathogen causing both mucosal (otitis media and pneumonia) and systemic (sepsis and meningitis) diseases. Due to increasing rates of antibiotic resistance, there is an urgent need to improve prevention of pneumococcal disease. Two currently licensed vaccines have been successful in reducing pneumococcal disease, but there are limitations with their use and effectiveness. Another approach for prevention is the use of live attenuated vaccines. Here we investigate the safety and protection induced by live attenuated strains of S. pneumoniae containing combinations of deletions in genes encoding three of its major virulence determinants: capsular polysaccharide (cps), pneumolysin (ply), and pneumococcal surface protein A (pspA). Both the cps and ply/pspA mutants of a virulent type 6A isolate were significantly attenuated in a mouse model of sepsis. These attenuated strains retained the ability to colonize the upper respiratory tract. A single intranasal administration of live attenuated vaccine without adjuvant was sufficient to induce both systemic and mucosal protection from challenge with a high dose of the parent strain. Immunization with cps mutants demonstrated cross-protective immunity following challenge with a distantly related isolate. Serum and mucosal antibody titers were significantly increased in mice immunized with the vaccine strains, and this antibody is required for full protection, as μMT mice, which do not make functional, specific antibody, were not protected by immunization with vaccine strains. Thus, colonization by live attenuated S. pneumoniae is a potentially safe and less complex vaccine strategy that may offer broad protection.